IMPLEMENTASI PENDIDIKAN KARAKTER BERBASIS NILAI-NILAI ISLAM DI SEKOLAH DASAR ISLAM TERPADU TAHUN PELAJARAN 2024-2025 (STUDI KASUS DI SD ISLAM TERPADU AL-IMAN BOJONGSARI DEPOK JAWA BARAT) - Ramadhan, Alfan Aziz; Cipto Handoko; Zainuri (UNISAN JURNAL, 2025)
This study aims to analyze the implementation of character education based on Islamic values ​​at Al-Iman Integrated Islamic Elementary School (SDIT) Bojongsari Depok in the 2024–2025 academic year. The research method used was qualitative with a case study approach. Data were obtained through interviews, observation, and documentation. The results showed that the implementation of character education was carried out through intracurricular, co-curricular, and extracurricular programs, as well as the habituation of daily worship and Islamic school culture. Character values ​​include honesty, discipline, responsibility, noble character, and social concern. Supporting factors for its implementation include the role of teachers, the religious environment, and systematic school programs. However, there are obstacles such as variations in student character, limited facilities, and consistency challenges. Overall, the character education program at SDIT Al-Iman is running effectively and has a positive impact on student character development. The focus of this paper is the application of character education based on Islamic values. Character education based on Islam means character education whose components include moral knowledge, moral feelings, and moral actions. These morals are explored and developed based on Islamic values. The application of this character education aims to shape students' Islamic and tolerant character. This research utilized a literature review. The results of this study indicate that the application of character education requires seriousness, habituation, and the inculcation of values.